2009
DOI: 10.1088/0957-4484/20/7/075703
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced shrinkage and expansion mechanisms of SiO2circle membrane nanopores

Abstract: 20 nm diameter SiO(2) nanopore arrays on gradient-thickness membranes were formed by a focused electron beam with in situ transmission electron microscopy (TEM). Nanopore shrinkage was seen in nanopores on thicker membranes, with the rate of diameter change remaining constant during the shrinkage process. In contrast, pore expansion was observed in thinner membranes, with the expansion rate being constant at the initial stage but with a slight increase at the later stage. The geometry model of shrinkage and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…4a–4c) (see Supplementary Movies S1–S2 online). Such nonlinear shrinking behavior is in contrast with knowledge revealed during the shrinkage of nanopores in SiO 2 , where the shrinking rate remained constant1017.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…4a–4c) (see Supplementary Movies S1–S2 online). Such nonlinear shrinking behavior is in contrast with knowledge revealed during the shrinkage of nanopores in SiO 2 , where the shrinking rate remained constant1017.…”
Section: Resultscontrasting
confidence: 73%
“…Noticeable expansion of the nanopore was not observed, which may be attributed to oxidation. Such size effects suggest that the surface-tension effect17 should be considered in the healing mechanism in Mg. However, the detailed relationship between the critical size and sample thickness is beyond the scope of the present study and will be studied in future research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Solid-state nanopores have been extensively investigated due to many biological engineering and scientific applications, such as for rapid electrical detection and analysis of biopolymers, 1-5 powerful DNA detection, and genome sequencing technology. 6,7 To date, nanopores were fabricated and studied in various materials including SiO 2 , 8,9 Si 3 N 4 , 10 Al 2 O 3 , 11 and graphene, 12 etc., via electron beam (e-beam) drilling 10,12 and ion beam sculpting. 13 It is interesting to note that most of the nanopores reported previously are circular with no obvious facets, as a result of the isotropic property in amorphous materials.…”
Section: Fabrication Of Faceted Nanopores In Magnesiummentioning
confidence: 99%
“…13 It is interesting to note that most of the nanopores reported previously are circular with no obvious facets, as a result of the isotropic property in amorphous materials. [8][9][10][11] While faceted nanopores can be potentially employed in rapid electrical detection and analysis of biomacromolecule with various shapes, the relevant investigation has been rarely reported. 14 In addition, Venta et al recently showed the synthesis of electrically controlled gold nanoparticles inside nanopores, 15 indicating that an individual nanopore can serve as a "nano-mold" regarding the synthesis of nanomaterials.…”
Section: Fabrication Of Faceted Nanopores In Magnesiummentioning
confidence: 99%